Indoor/outdoor not-voluptuary-habit pollution and sleep-disordered breathing in children: a systematic review - Tenero, Laura; Piacentini, Giorgio; Nosetti, Luana; Gasperi, Emma; Piazza, Michele; Zaffanello, Marco (Translational Pediatrics; Vol 6, No 2 (April 19, 2017): Translational Pediatrics, 2017)
Background: Exposure to environmental pollutants is advocated to be a major risk factor, with increased morbidity and mortality in humans due to acute and chronic airway inflammation. The aim of the present review is to show the literature research regarding the link between the sleep-disordered breathing and exposure to indoor/outdoor pollution in children. We hypothesized that environmental air pollution can play a role in childhood sleep-disordered breathing. Methods: We conducted an electronic search in Medline (with PubMed interface), Scopus and the ISI Web of Science using the keywords “sleep” or “sleep apnea” or “sleep disordered breathing” and “pollution” and “children” in “Title/Abstract/Keywords”, with language restriction (non-English paper) and no date limitation to present. The tobacco smoke pollution is well established linking and is not considered for the present subject. We examined the strength of the evidence according to the Oxford Centre for Evidence-Based Medicine [2011] and the Centre for Evidence-Based Medicine [2009]. Results: A total of 105 articles were identified, but 97 of these had to be excluded after an accurate reading of the title, abstract or full text. In the end, eight studies were selected for our analysis for a total of a total of 5,826 children. The results suggest an involvement (grade C) of environmental (not from voluptuary habits) pollution in the worsening of sleep-disordered breathing in children. Conclusions: To date, some studies reported significant differences between areas with higher and lower pollutants and the interventions on indoor pollution reduced sleep-disordered breathing in children. Therefore, although the relevance of the argument is high, the number of studies and the interest in the subject seems at this time quite limited.